Towards Green and Climate-Resilient Urbanization in Rajshahi City: Urban Growth Meets Climate Action in Northern Bangladesh - Md. Shafiul ALAM; Md. Abdullah AL MAMUN; Md. Ashikur RAHMAN; Rumana SULTANA; Md. SALAUDDIN; Naimur RAHMAN; Mst. Rebeka SULTANA; Mostofa Tarequl AHSAN (Chinese Journal of Urban and Environmental Studies)
Climate change and rapid urbanization pose significant challenges, necessitating novel approaches to creating sustainable and resilient cities. Many studies illustrate that unplanned and spontaneous urbanization is emerging without sufficient planning, posing grave risks to urban infrastructures, including water systems and biodiversity. This paper explores strategies for attaining green and climate-resilient urbanization in Northern Bangladesh by examining the relationship between urban expansion and climate action in Rajshahi city. A comprehensive systematic literature review, field observation, the city corporation information hub, remote sensing data, and geospatial analytic techniques and processes were used to carry out this study. Rajshahi city is especially exposed to the adverse effects of climate change and environmental stresses, including hazardous, severe heat waves. The investigation discovered that several factors, including the city’s rapid urbanization and the adverse effects of climate change, the growth of concrete infrastructure, deforestation, the depletion of water bodies, an increase in dry and impervious surfaces, and a variety of commercial activities, exacerbate the heat island effect. The Rajshahi city authority recently took several initiatives to help the city become green and climate-resilient through the Climate-Resilient City Action Plan (CRCAP). Several aspects of this project’s urban transformation, including the development of heat-resilient infrastructure and the extension of urban green space alongside roadways, have received domestic and international recognition for their effectiveness in mitigating the heat impact and tackling climate change challenges. However, Rajshahi’s complex crisis requires a coordinated national and local policy agenda and active city governance strategies. The results of this study can help inform environmentally conscious and climate-resilient decision-making in Rajshahi city and similar places around the world.